Unearthed 2016
DOI: 10.2307/j.ctt1g69w6r.33
|View full text |Cite
|
Sign up to set email alerts
|

The use of aero-magnetics to enhance a numerical groundwater model of the Lagan Valley aquifer, Northern Ireland

Abstract: Numerical modelling of aquifers is a standard process in the sustainable management of groundwater resources. To be reliable, a groundwater model requires an accurate geological framework, particularly where structure is complex. The Lagan Valley aquifer near Belfast is an example of an otherwise generally homogenous sandstone aquifer intruded by extensive swarms of low-permeability igneous dykes. The dissection of the aquifer by these dykes affects groundwater flow direction and borehole yield. We have used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…There is also a need to test this method in alternative geological settings which will have different heterogeneity conditions and structure, e.g., higher permeability features in hardrock/basement or karstic context, in particular where structure than cannot be assumed to be “banded.” Alternative AMag realizations are also needed, perhaps through utilization of stochastic methods and multiple‐point statistics (MPS). This can analyze the aerial geophysics to provide many equally probabilistic alternatives of AMag distribution in order to improve the lineament computation particularly in noisy regions [ Dickson et al , ]. The deterministic and equivalent field model and parameters may continue to be used as equivalence for this new interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a need to test this method in alternative geological settings which will have different heterogeneity conditions and structure, e.g., higher permeability features in hardrock/basement or karstic context, in particular where structure than cannot be assumed to be “banded.” Alternative AMag realizations are also needed, perhaps through utilization of stochastic methods and multiple‐point statistics (MPS). This can analyze the aerial geophysics to provide many equally probabilistic alternatives of AMag distribution in order to improve the lineament computation particularly in noisy regions [ Dickson et al , ]. The deterministic and equivalent field model and parameters may continue to be used as equivalence for this new interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…This is exemplified by the recent regional modeling study of the Sherwood sandstone aquifer by Dickson et al . []. In these studies, observed field‐scale hydrodynamic properties of the dykes enabled the estimation of regional properties of dyke clusters of varying densities applied to a 100 km‐scale groundwater flow model.…”
Section: Discussionmentioning
confidence: 99%